The Relationship of Early Complementary Feeding (CF) with Nutritional Status to Children Aged 6-24 Months towards Family Farmers - Lutfian, Lutfian; Juliningrum, Peni Perdani; Kurniawati, Dini (Universitas Pendidikan Indonesia, 2021)
ABSTRACTIntroduction. Complementary feeding (CF) practices have an essential role in determining the nutritional status of children. Children who are given early complementary feeding (ECF) are at risk of malnutrition. Besides, children with family farmers tend to have wasting or overweight because they cannot provide food in a variety, quantity, and quality according to the nutritional needs of their children. Objectives: This study aimed to determine the relationship of ECF with nutritional status in children 6-24 months towards family farmers. Methods. This correlational study was conducted using a cross-sectional approach. Samples were 75 children aged 6-24 months selected using purposive sampling. This research was conducted at Geger Health Center Bangkalan Regency. Data collection was done by giving questionnaires to children parents. Children's weight-for-height z-score (WHZ) were calculated using WHO Anthro version application 3.2.2. The chi-square test analyzed the association between CF and nutritional status. Result. The results of the study showed that the nutritional status of 75 children was normal (72%), overweight (25,3%), and wasted (2,7%). Most mothers have been given ECF since infants aged two months (29,3%) and 0 months (13%), which caused 36,4% of children to become overweight. Bivariate analysis showed a significant relationship between CF with nutritional status to children aged 6-24 months towards family farmers (p-value=0,033). Discussion. ECF caused children aged 6-24 months to become overweight. Therefore, it is hoped that health workers will always give health education to increase mothers' knowledge about exclusive breastfeeding to support the nutritional status of children aged 6-24 months towards family farmers.Â ABSTRAKPendahuluan. Praktik pemberian makanan pendamping ASI (MP-ASI) memiliki peranan yang penting dalam menentukan status gizi anak usia 6-24 bulan. Anak yang diberikan MP-ASI dini memiliki risiko tinggi untuk mengalami malnutrisi. Disamping itu, anak dengan keluarga petani cenderung mengalami status gizi buruk atau lebih, karena mereka tidak diberikan makanan dengan variasi, kuantitas, dan kualitas yang sesuai dengan kebutuhan anak mereka. Tujuan.Â Tujuan penelitian ini menganalisis hubungan pemberian MP-ASI dini dengan status gizi anak usia 6-24 bulan pada keluarga petani. Metode. Penelitian ini menggunakan desain penelitian korelational dengan pendekatan cross-sectional. Jumlah sampel dalam penelitian ini adalah 75 anak usia 6-24 bulan yang diseleksi menggunakan metode purposive sampling. Peneliti melakukan penelitian di wilayah kerja Puskesmas Geger Kabupaten Bangkalan. Data dikumpulkan menggunakan kuisioner untuk mengetahui karakteristik responden dan riwayat pemberian MP-ASI. Indikator berat badan menurut Panjang badan (BB/PB) di hitung menggunakan aplikasi WHO Anthro versi 3.2.2. Untuk menganalisis hubungan pemberian MP-ASI dengan status gizi peneliti menggunakan uji chi-square. Hasil. Hasil penelitian ini menunjukkan bahwa 72% dari 75 anak memiliki status gizi normal, 25,3% status gizi lebih, dan 2,7% status gizi kurang. Kebanyakan ibu telah memberikan MP-ASI dini sejak bayi berusia 2 bulan (29,3%) dan 0 bulan (13%) dan hal ini menyebabkan 36,4% anak mengalami status gizi lebih. Analisis bivariat menunjukkan hubungan yang signifikan antara pemberian MP-ASI dengan status gizi anak usia 6-24 bulan pada keluarga petani (p-value=0,033). Diskusi. Pemberian MP-ASI dini menyebabkan anak Â usia 6-24 bulan mengalami kejadian gizi lebih. Oleh karena itu, diharapkan agar tenaga kesehatan dapat memberikan promosi Kesehatan untuk meningkatkan pengetahuan tentang pemberian ASI ekslusif untuk mendukung status gizi anak usia 6-24 tahun pada keluarga petani.